2016
DOI: 10.1007/s10864-016-9254-3
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of a Brief Multiple-Stimulus Without Replacement Preference Assessment Conducted in an Electronic Pictorial Format

Abstract: We compared the results of a brief electronic pictorial multiple-stimulus without replacement (EP-MSWO) preference assessment to a brief tangible MSWO preference assessment in five children with autism. Results of both assessments yielded a match between high preferred (HP) toys for four participants and low preferred toys for three participants. The overall correlation between assessments across participants was strong and statistically significant (q = .67, p \ .01). A reinforcer assessment conducted with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 21 publications
(25 reference statements)
1
13
0
Order By: Relevance
“…Behavior analysts have long taken advantage of emerging technology and benefitted from doing so (Cohen & Rozenblat, ). The present data, combined with those of prior investigations (Brodhead, Abel, et al, ; Brodhead et al, ; Brodhead, Al‐Dubayan, et al, ; Chebli & Lanovaz, ; Curiel et al, ; Snyder, Higbee, & Dayton, ; Whitehouse, Vollmer, & Colbert, ), demonstrate that technology‐based applications provide a viable means for conducting preference assessments for a variety of stimuli and for assessing the reinforcing efficacy of those stimuli. When those stimuli are videos, rather than video depictions of objects that will be made available at a later time, the automated device could be used to deliver putative reinforcers during interventions.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Behavior analysts have long taken advantage of emerging technology and benefitted from doing so (Cohen & Rozenblat, ). The present data, combined with those of prior investigations (Brodhead, Abel, et al, ; Brodhead et al, ; Brodhead, Al‐Dubayan, et al, ; Chebli & Lanovaz, ; Curiel et al, ; Snyder, Higbee, & Dayton, ; Whitehouse, Vollmer, & Colbert, ), demonstrate that technology‐based applications provide a viable means for conducting preference assessments for a variety of stimuli and for assessing the reinforcing efficacy of those stimuli. When those stimuli are videos, rather than video depictions of objects that will be made available at a later time, the automated device could be used to deliver putative reinforcers during interventions.…”
Section: Discussionsupporting
confidence: 75%
“…Whether his performance was due to a failure to understand instructions, a true lack of preference among the videos, or some other factor is unknown. Within any modality of item presentation, whether it be videos, video representations of activities (Brodhead, Abston, Mates, & Abel, ), or actual tangibles (Brodhead, Abel, et al, ; Kang et al, ), an occasional participant fails to demonstrate clear preferences when exposed to brief MSWOs, full MSWOs, or other (see Roscoe et al, ) assessment procedures. Further research is warranted to examine why this occurs and how web‐based procedures can be modified to yield interpretable results in all participants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, targeting and evaluating generalization with children with ASD is crucial in any intervention program. However, not all studies evaluated the generalization of taught concepts with a computer to new untaught exemplars (e.g., Moore & Calvert, 2000) and those that have typically used images of the concepts (e.g., Bosseler & Massaro, 2003; Whalen et al, 2006).Studies on the validity of preference assessments have shown that some children with ASD may readily show generalization across modalities from pictures (or videos) to objects when identifying potential reinforcers (Brodhead et al, 2016;Clark, Donaldson, & Kahng, 2015; GENERALIZATION FOLLOWING TABLET-BASED INSTRUCTION 6 Snyder et al, 2012). That said, it is was not always the case, and to our knowledge, no study has evaluated whether children with ASD were able to generalize between concepts taught using a two-dimensional modality (e.g., images) to their corresponding objects outside the context of reinforcement.…”
mentioning
confidence: 99%
“…Studies on the validity of preference assessments have shown that some children with ASD may readily show generalization across modalities from pictures (or videos) to objects when identifying potential reinforces (Brodhead et al, 2016; Clark, Donaldson, & Kahng, 2015; Snyder, Higbee, & Dayton, 2012). That said, it is was not always the case, and to our knowledge, no study has evaluated whether children with ASD were able to generalize between concepts taught using a two-dimensional modality (e.g., images) to their corresponding objects outside the context of reinforcement.…”
mentioning
confidence: 99%